2021
DOI: 10.1371/journal.pone.0245481
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized, open-label, parallel, multi-center Phase IV study to compare the efficacy and safety of atorvastatin 10 and 20 mg in high-risk Asian patients with hypercholesterolemia

Abstract: Background Although accumulating evidence suggests a more extensive reduction of low-density lipoprotein cholesterol (LDL-C), it is unclear whether a higher statin dose is more effective and cost-effective in the Asian population. This study compared the efficacy, safety, and cost-effectiveness of atorvastatin 20 and 10 mg in high-risk Asian patients with hypercholesterolemia. Methods A 12-week, open-label, parallel, multicenter, Phase IV randomized controlled trial was conducted at ten hospitals in the Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our searches identified 11,973 citations (11,869 from database searches and 104 from previous meta-analyses). Finally, after assessing the full text, forty-seven eligible studies ( 25 71 ) were included ( Figure 1 ). Supplementary Table 3 presents the list of studies excluded after assessing the full text and reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Our searches identified 11,973 citations (11,869 from database searches and 104 from previous meta-analyses). Finally, after assessing the full text, forty-seven eligible studies ( 25 71 ) were included ( Figure 1 ). Supplementary Table 3 presents the list of studies excluded after assessing the full text and reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In a randomized, multicenter phase 4 study to compare the efficacy and safety of atorvastatin 10 and 20 mg in high‐risk Korean patients with hypercholesterolemia, the LDL‐C levels were reduced more significantly by atorvastatin 20 mg than by 10 mg after 12 weeks (42.4% versus 33.5%; P <0.0001). 36 To evaluate the long‐term laboratory efficacy and safety of high‐ and low‐dose FDC of amlodipine and atorvastatin, we previously conducted a retrospective, multi‐institutional, real‐world, electronic medical record–based study that demonstrated that an FDC of 5 mg of amlodipine and 20 mg of atorvastatin daily significantly reduced the LDL‐C level when compared with a similar FDC that only contained 10 mg of atorvastatin (−35.7 versus −23.6 mg/dL; regression coefficient, −2.7 [95% CI, −4.3 to −1.2]; P <0.001), and the medication adherence rate did not differ between these 2 regimens in patients with concurrent hypertension and hypercholesterolemia. 22 However, the incidence of MACEs in that study was not significantly different between high and low doses of the amlodipine/atorvastatin FDC, which may be the result of the short follow‐up period and restricted events only recorded in our multi‐institutional database.…”
Section: Discussionmentioning
confidence: 99%